2022
DOI: 10.3389/fpsyt.2022.920665
|View full text |Cite
|
Sign up to set email alerts
|

Lower serum levels of IL-1β and IL-6 cytokines in adolescents with anorexia nervosa and their association with gut microbiota in a longitudinal study

Abstract: IntroductionAnorexia nervosa (AN) is an often chronic and debilitating psychiatric disease whose etiology is not completely understood. Recently, a potential role of inflammation has emerged in other psychiatric diseases, such as depression, PTSD and schizophrenia. The first results in adults with AN seemed to confirm a low-grade proinflammatory state until recent studies presented more differential findings. Studying adolescents with a shorter illness duration and fewer confounding factors might help elucidat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 90 publications
1
10
1
Order By: Relevance
“…In the consideration of our findings, it is important to note that concentrations of IL-6, TNF-α, and BDNF were not found to be different between acAN-TP1 and HC, partially contrasting with the previous literature (Dalton et al, 2018;Keeler et al, 2022) but aligning with more recent research findings that account for potentially confounding variables (e.g. smoking status, psychotropic medication; Keeler et al, 2021a;Specht et al, 2022). Moreover, concentrations of IL-6 did not decrease with weight restoration, contrasting with a prior study (Dalton et al, 2020).…”
Section: Psychological Medicinecontrasting
confidence: 99%
“…In the consideration of our findings, it is important to note that concentrations of IL-6, TNF-α, and BDNF were not found to be different between acAN-TP1 and HC, partially contrasting with the previous literature (Dalton et al, 2018;Keeler et al, 2022) but aligning with more recent research findings that account for potentially confounding variables (e.g. smoking status, psychotropic medication; Keeler et al, 2021a;Specht et al, 2022). Moreover, concentrations of IL-6 did not decrease with weight restoration, contrasting with a prior study (Dalton et al, 2020).…”
Section: Psychological Medicinecontrasting
confidence: 99%
“…In their study on 22 patients with AN, Specht et al (2022) observed an inverse relationship between changes in proinflammatory cytokines and specific microbial taxa possessing well-documented anti-inflammatory properties, such as Lachnospiraceae and Anaerostipes . Notably, the increased abundance of Lachnospiraceae during short-term weight recovery could potentially contribute to the reduction in TNF-α levels [ 106 ]. Previous research has linked Lachnospiraceae to favourable effects on cardiovascular risk factors and anti-inflammatory effects in the context of inflammatory bowel disease [ 107 , 108 ].…”
Section: Resultsmentioning
confidence: 99%
“…These findings collectively suggest the potential for a bidirectional interdependence between gut microbiota and inflammation in individuals with AN. The observed associations between specific microbial taxa and proinflammatory processes may hold valuable insights into the intricate relationship between gut microbiota composition and inflammatory states in AN [ 106 ].…”
Section: Resultsmentioning
confidence: 99%
“… 50 , 51 Patients with AN are thought to have chronic low-grade inflammation of unknown origin (meta-analysis by 52 ); however, recent findings are more diverse and show variable dysregulation of the immunologic state. 53 , 54 AN is also associated with an increased rate of autoimmune diseases, especially Crohn’s disease and celiac disease. 55 , 56 Therefore, the immunomodulatory effects of these taxa might be important for their mechanistic role in AN outcomes.…”
Section: Discussionmentioning
confidence: 99%